2006
DOI: 10.1097/01.ta.0000204022.36214.9e
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Trauma Systems: Do They Improve Triage or Outcomes of the Severely Injured?

Garth H. Utter,
Ronald V. Maier,
Frederick P. Rivara
et al.

Abstract: Severely injured trauma patients have greater inpatient survival in inclusive trauma systems even though they are no more likely to be hospitalized at a regional trauma center. Consideration should be given to continuing implementation of systems with an inclusive configuration, especially in light of other theoretical benefits of these systems, such as better dispersing of trauma care resources in the event of natural disasters or terrorist events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(100 citation statements)
references
References 20 publications
3
92
0
4
Order By: Relevance
“…1 In the past 4 decades, regionalized trauma care has been promoted in the U.S. as the best approach for matching patient needs with the available resources and provider expertise to achieve optimal patient outcomes. [2][3][4][5] Previous research has shown that trauma centers achieve better outcomes among severely injured patients than non-trauma centers; however, it has been found that about one-third of patients with severe injuries were treated at nontrauma centers or level III trauma centers. 3,6 Transportation to the hospital via Emergency Medical Service (EMS) is important in caring for trauma patients for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…1 In the past 4 decades, regionalized trauma care has been promoted in the U.S. as the best approach for matching patient needs with the available resources and provider expertise to achieve optimal patient outcomes. [2][3][4][5] Previous research has shown that trauma centers achieve better outcomes among severely injured patients than non-trauma centers; however, it has been found that about one-third of patients with severe injuries were treated at nontrauma centers or level III trauma centers. 3,6 Transportation to the hospital via Emergency Medical Service (EMS) is important in caring for trauma patients for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…25 However, the use of more inclusive trauma systems appears to mitigate these effects. 26 This mitigation is probably the result of having lower-level centers ready to resuscitate patients and initiate treatment of major injuries, as well as broad acceptance of systemwide protocols that expedite transfer when appropriate.…”
Section: Costs and Benefits Of Trauma Systemsmentioning
confidence: 99%
“…[5][6][7][8] Studies of trauma system effectiveness have reported improved patient survival, particularly among seriously injured patients, and reduced time to definitive institutional trauma care. 2,[9][10][11][12][13][14][15][16][17][18][19][20][21][22] The importance of trauma systems concepts and the key role they play in obviating the enormous burden of injury in society has been demonstrated in numerous studies, reviews and editorials but is rarely a studied health care issue in Canada. 13,[20][21][22][23][24][25][26] Between 1995 and 1998, the province of Nova Scotia, Canada, underwent a government-mandated transition from a province without a trauma system to one incorporating most of the components of a modern trauma and emergency medical service (EMS) system.…”
Section: Discussionmentioning
confidence: 99%